Formulating the African National Congress' foreign investment policy in the transition to a post-apartheid South Africa: problems, pressures and constraints - Carim, Xavier (Rhodes University, Faculty of Humanities, Department of Political Studies, 1995)
This study examines the wide-ranging and critical factors which have impacted on the African National Congress' (ANC) emerging foreign investment policy. It identifies and analyses the matrix of political and socio-economic factors which have combined at global and national levels to shape ANC policy perspectives towards foreign direct investment (FDI). In so doing, the study adopts an eclectic theoretical and methodological approach. It draws on various theoretical traditions to propose a framework that is heuristic and contingent, rather than axiomatic. With regard to foreign investment, in particular, it recommends a theoretical pluralism emphasising 'engagement' through praxis and sound political (state) action. The study argues that the ANC has reconsidered many of its basic assumptions on the nature of the post-apartheid economy and discusses the reasons for those shifts. The reasons include, in particular, global political and economic trends and the balance of forces in South Africa. These have combined to ensure the ANC's broad acceptance of an 'open-door policy' towards FDI so long as it occurs on terms not inconsistent with national objectives. The emerging policy sees the state playing an active role in encouraging and guiding FDI to specific areas and sectors supportive of broad-based development. Foreign investors will be encouraged to form joint ventures with emerging black businesses and agree to foster training, skills development and affirmative action. Harnessing the benefits of FDI will be important for the success of wider strategies designed to place the economy on a firmer, more sustainable growth path.
Keywords: Investments, Foreign -- South Africa|Political stability -- South Africa|African National Congress -- Foreign economic relations|South Africa -- Foreign economic relations|South Africa -- Economic policy|South Africa -- Economic conditions -- 1991-